An Unusual Case Of Talonavicular Dislocation With Associated Ipsilateral Foot Fractures. Issue 2 (1st June 2006) - Ede, Newton; Miller, C; Malik, MHA; Khan, SA
Abstract : We describe a previously unreported form of a talonavicular dislocation complicated by navicular, talar neck and open calcaneal fractures. Prompt recognition and rapid reduction of fractures and dislocations gives the best possible outcome. The presence of serious distracting injuries can alter priorities, however the "lesser" injuries often lead to long term morbidity after recovery from the life-threatening injuries.